1991
DOI: 10.1002/1097-0142(19910915)68:6+<1426::aid-cncr2820681404>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin subclasses and prophylactic use of immunoglobulin in immunoglobulin g subclass deficiency

Abstract: Persistent low serum levels of one or several immunoglobulin G (IgG) subclasses can be found in a high proportion of adult patients with increased susceptibility to infections. It is hard to envision that the low subclass level in itself is responsible for this susceptibility because healthy blood donors have been described who are completely devoid of certain subclasses in serum. This apparent discrepancy may be partly explained by the observation that most subclass‐deficient patients have underlying aberrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…These results are consistent with previous studies that have reported IgG subclass deficiency in patients with bronchial asthma or obstructive lung disease (16-18). Other studies have revealed that more than 40% of subjects with IgG3 subclass deficiency have a history of asthma (19) and 41-50% of severe asthmatic children showed IgG3 subclass deficiency (16). Low levels of IgG subclasses have been associated with an increased susceptibility to respiratory infections, especially during primary immune responses to viral protein antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with previous studies that have reported IgG subclass deficiency in patients with bronchial asthma or obstructive lung disease (16-18). Other studies have revealed that more than 40% of subjects with IgG3 subclass deficiency have a history of asthma (19) and 41-50% of severe asthmatic children showed IgG3 subclass deficiency (16). Low levels of IgG subclasses have been associated with an increased susceptibility to respiratory infections, especially during primary immune responses to viral protein antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice for antibody deficiency is intravenous immunoglobulin (IVIG) replacement therapy (19, 29, 30). Adequate replacement of IVIG has been shown to reduce the incidence of pneumonia and prevent the progression of lung disease in patients with PID.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the useful role of regular IVIG therapy for prophylaxis against infections [9,10]. However, in developing countries, regular therapy is difficult because of issues such as cost, brief hospital admission required for administration of immunoglobulins, patient compliance with scheduling and possibility of contamination of the product given [10].…”
Section: Discussionmentioning
confidence: 99%
“…6,38,39 Silk et al 40 reported that in children with IgG2 subclass and specific antibody deficiency who failed to improve after a 12-month period of prophylactic antibiotic therapy with trimethoprim-sulfamethoxazole, IVIG therapy significantly decreased the number of episodes of recurrent sinopulmonary infections. Similarly, Bernatowska-Matuszkiewicz et al 39 demonstrated the clinical efficacy of IVIG in pediatric patients with severe pulmonary inflammatory disease and IgG3 subclass deficiency by decreasing the duration of hospitalization and use of antibiotics and steroids.…”
Section: Discussionmentioning
confidence: 99%